Diagnostic Challenge of Tuberculosis Heterogeneity - Nemes, Elisa; Meermeier, Erin W.; Scriba, Thomas J.; Walzl, Gerhard; Malherbe, Stephanus T.; Lewinsohn, David M. (Seminars in Respiratory and Critical Care Medicine, 2018)
For the ICU physician, the failure to consider, diagnose, and treat tuberculosis (TB) results in increased morbidity and mortality, and poses risks to both patients and health care providers. At present, the diagnosis of TB depends on the detection of either mycobacteria or mycobacterial products from clinical specimens. Given the risks posed to both the patient and health care providers by undiagnosed and/or untreated TB, the ability to diagnose TB rapidly in the ICU cannot be understated. In this regard, nucleic acid amplification tests provide relatively quick information about the presence of Mycobacterium tuberculosis (Mtb) DNA. If available, a blood-based test that would accurately identify persons with TB would be of use in the ICU. Currently available tests such as the T-Spot.TB or QuantiFERON-TB Gold In-Tube can discern infection with Mtb, but are not recommended for the ICU as they cannot rule out TB. In this review, we will discuss the increasing literature that would suggest that a blood-based diagnostic that reflects the host response to TB could be used to diagnose TB in the ICU.
Keywords: tuberculosis; diagnosis; subclinical; host response